Dental Health Status of Children in the Jember Regency's Agroindustry Environment - Sulistiyani Sulistiyani; Dyah Setyorini; Akhmad Syahrul Mubarok (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2022)
Caries is one of the most common dental health issues, particularly in children. Caries develops over time due to the interaction of bacteria on the tooth surface, plaque or biofilm, and diet, resulting in the demineralization of hard tooth tissue. School-age children frequently consume food and beverages with no knowledge of which foods and beverages may increase the risk of dental caries. This study aims to identify the ICDAS caries index used to describe children's dental health status in Nogosari Elementary School grades I-III. Descriptive observational research with a cross-sectional approach was used. The sample in this study consisted of 76 students from grades I-III, employing the total sampling method. The collected data were entered into the examination form, discussed descriptively, and presented in tabular form. There were 823 caries-free teeth and 929 carious teeth in each unit. Caries reaching the pulp (ICDAS code 6) were the most severe caries found in children, affecting 50 children. As a result, there were no caries-free children. The dental health of Negeri Nogosari Elementary School children's of grades I-III in Kebun Renteng's agro-industrial environment was relatively poor. The number of caries-infected teeth was 53% higher than the number of caries-free teeth. There were no caries-free children in grades I-III, and the most severe dental caries discovered were caries that reached the pulp (ICDAS code 6).